Composition-dependent phase transformation in side-chain liquid crystalline copolymers with mesogenic groups at different substituent positions. Issue 17 (13th April 2021) - Pei, Jiwei; Wei, Wenjing; Li, Bian; Huang, Jundan; Chen, Xiao-Fang
Abstract : The composition and chemical structures have important effects on the evolution of supramolecular liquid crystalline structures in SCLC copolymers. Abstract : Copolymerization is an effective approach to tailor the thermal and structural properties of liquid crystalline polymer materials, which is essential for various applications. In this work, two series of polynorbornene copolymers, A- r -B and A- r -C, with the biphenyl mesogenic side group at different substituent positions were synthesized via ring-opening metathesis polymerization in various compositions. The corresponding homopolymers A and C are liquid crystalline polymers, exhibiting an oblique columnar structure (Colob / p 2) and lamellar structure, respectively, while homopolymer B is amorphous. The composition-dependent phase behaviors of copolymers were systematically studied with the combination of SAXS, GISAXS, AFM, DSC and POM techniques. With increasing molar content of A ( x A ), the self-organzied structure of copolymer A- r -B follows the sequence from amorphous to lamellar, undulated lamellar, and Colob / p 2 structures, and that of A- r -C follows the sequence of lamellar, undulated lamellar, and Colob / p 2 structures. Then, copolymers with undulated lamellar or Colob / p 2 structures tend to enter lamellar phase first at higher temperature and then change to the isotropic state during heating. The composition-induced transition from lamellar to supramolecular columnar organization is somewhat reminiscent of block copolymers and other soft matter systems that can form ordered structures. Furthermore, the subsitituent number and position of rigid mesogenic units in the side chain can further modify the morphologies of self-organized phases.